PH‐Responsive Charge‐Conversion Progelator Peptides. (14th January 2021) - Carlini, Andrea S.; Choi, Wonmin; McCallum, Naneki C.; Gianneschi, Nathan C.
Abstract: A simple strategy for generating stimuli‐responsive peptide‐based hydrogels via charge‐conversion of a self‐assembling peptide (SAP) is described. These materials are formulated as soluble, polyanionic peptides, containing maleic acid, citraconic acid, or dimethylmaleic acid amide masking groups on each lysine residue, which do not form assemblies, but instead flow easily through high gauge needles and catheters. Acid‐induced mask hydrolysis renews the zwitterionic nature of the peptides with concomitant and rapid self‐assembly via β‐sheet formation into rehealable hydrogels. The use of different masks enables one to tune pH responsiveness and assembly kinetics. In anticipation of their potential for in vivo hydrogel delivery and use, progelators exhibit hemocompatibility in whole human blood, and their peptide components are shown to be noncytotoxic. Finally, demonstration of stimuli‐induced self‐assembly for dye sequestration suggests a simple, non‐covalent strategy for small molecule encapsulation in a degradable scaffold. In summary, this simple, scalable masking strategy allows for preparation of responsive, dynamic self‐assembling biomaterials. This work sets the stage for implementing biodegradable therapeutic hydrogels that assemble in response to physiological, disease‐relevant states of acidosis. Abstract : A simple strategy for generating structurally dynamic stimuli‐responsive peptide‐based hydrogels is developed. By utilizing charge‐conversional masking groups, zwitterionic gelator peptides can be formulated as soluble, polyanionic progelators for initial catheter or needle‐based delivery. Tunable responsiveness to an acidic environment regenerates the initial gelator, providing a scalable strategy for implementing biodegradable therapeutic hydrogels that assemble at sites of disease‐related tissue acidosis.